MICU1 controls cristae junction and spatially anchors mitochondrial Ca2+ uniporter complex - Benjamin Gottschalk (Nature Portfolio, 2019)
Proper mitochondrial structure is critical for normal function. Here, the authors show with SIM that the mitochondrial Ca2+ uniporter complex and localization of component MICU1 is critical to maintaining cristae junction stability and overall mitochondrial membrane structure.